Neuroscience in the HBSE Sequence: Mandate and Methodology. Issue 5 (20th October 2017) - Combs-Orme, Terri; Lefmann, Tess; Pilkay, Stefanie; Strong, Joe; Thompson, Phyllis; Veerman, Tara
ABSTRACT: Important findings from neuroscience research provide valuable knowledge for social work practice, and although these findings are already being incorporated into practice in many other disciplines, social work has been slow to integrate this content into foundation professional education. This article describes how one social work program incorporated this knowledge into Human Behavior in the Social Environment courses, noting both challenges and successes over 8 years. The authors include information on content, pedagogical methods, and useful resources.